What do we think life is? A simple illustration and its consequences. Issue 2 (April 2014) - Bains, William; Cockell, Charles; Burchell, Mark; Martins, Zita
Abstract The conundrum of finding a 'definition' for life can be side-stepped by asking how people actually identify examples of life, and using this as the basis for life detection strategies. I illustrate how astrobiologists actually select things that are living from things that are not living with a simple exercise, and use this as the starting point to develop four characteristics that underlie their decisions: highly distinctive structure (physical or chemical), dynamic behaviour (physical or chemical), multiple instances of life forming a 'natural group' and that the structural and dynamic characteristics of the group are independent of the details of the substrate on which life is growing. I show that these all derive the role of a code in the dynamic maintenance and propagation of life. I argue that evolution is neither a useful nor a practical way of identifying life. I conclude with some specific ways that these general categories of the observable properties of life can be detected.